MPPED2 is downregulated in glioblastoma, and its restoration inhibits proliferation and increases the sensitivity to temozolomide of glioblastoma cells. Issue 7 (3rd April 2021) - Pellecchia, Simona; De Martino, Marco; Esposito, Francesco; Quintavalle, Cristina; Fusco, Alfredo; Pallante, Pierlorenzo
ABSTRACT: Glioblastoma (GBM) is the most aggressive and lethal neoplasia of the central nervous system in adults. Based on the molecular signature genes, GBM has been classified in proneural, neural, mesenchymal and classical subtypes. The Metallophosphoesterase-domain-containing protein 2 ( MPPED2 ) gene encodes a metallophosphodiesterase protein highly conserved throughout the evolution. MPPED2 downregulation, likely due to its promoter hypermethylation, has been found in several malignant neoplasias and correlated with a poor prognosis. In this study, we aimed to investigate the expression and the functional role of MPPED2 in GBM. TCGA and Gravendeel databases were employed to explore the MPPED2 expression levels in this type of tumor. We have found that MPPED2 expression is downregulated in GBM patients, showing a positive correlation with survival. Moreover, TCGA and Gravendeel data also revealed that MPPED2 expression negatively correlates with the most aggressive mesenchymal subtype. Additionally, the restoration of MPPED2 expression in U251 and GLI36 GBM cell lines decreases cell growth, migration and enhanced the sensitivity to the temozolomide, inducing apoptotic cell death, of GBM cells. These findings suggest that the restoration of MPPED2 function can be taken into consideration for an innovative GBM therapy.